The Interactional Construction of Social Authenticity: "Real" Identities and Intergroup Relations in a Transylvania Internet Forum. Issue 2 (3rd April 2017) - Weninger, Csilla; Williams, J. Patrick
Abstract : Authenticity has become an increasingly salient topic within various interactional traditions, including conversational and discourse analysis, discursive psychology, interactional sociolinguistics, pragmatics, and symbolic interactionism. However, there has been remarkably little cross‐fertilization of ideas and concepts. In this study, we consider the relevance of the interactional sociolinguistic concept of relationality for symbolic interactionist theories of authenticity. We first disambiguate two forms of authenticity that are commonly studied but not clearly differentiated in symbolic interactionist research—self‐authenticity, which emphasizes selves, and social authenticity, which emphasizes social identities. We then argue that relationality and its three pairs of interactional tactics—verification and denaturalization, adequation and distinction, and authorization and illegitimation—are particularly useful in conceptualizing social authenticity. We draw on data from an interethnic internet forum to show how members of two ethnic groups, Hungarian and Romanian, employ these relational tactics to authenticate their own ethnicity as the rightful inheritors of a place‐based Transylvanian identity, and to limit the other ethnicity's similar identity work. We then clarify the significance of social authenticity for the interactional study of category‐based identities by widening our discussion to other contestations over social identities in everyday life.